English Language Pedagogies for the Northeast Asian Learner. - Hadzantonis, Michael (Routledge studies in sociolinguistics., 2013)
This book investigates, from a sociocultural, linguistic, and pedagogical perspective, the conceptual and pragmatic frameworks that characterize secondary language learning in a Northeast Asian context. Hadzantonis contextualizes these salient domains through an engagement with social and cultural themes such as the familial, political, as well as cultural commodities and socioeducational structures. In this way, the text employs tools such as transnational theory and performativity and develops a model that contributes to the resolution of one of the greatest economic issues of the time, t.